Disease-Associated Regulation of Non-Coding RNAs by Resveratrol: Molecular Insights and Therapeutic Applications - Giordo, Roberta; Wehbe, Zena; Posadino, Anna Maria; Erre, Gian Luca; Eid, Ali H.; Mangoni, Arduino A.; Pintus, Gianfranco (Frontiers in Cell and Developmental Biology, 2022)
There have been significant advances, particularly over the last 20 years, in the identification of non-coding RNAs (ncRNAs) and their pathophysiological role in a wide range of disease states, particularly cancer and other chronic conditions characterized by excess inflammation and oxidative stress such as atherosclerosis, diabetes, obesity, multiple sclerosis, osteoporosis, liver and lung fibrosis. Such discoveries have potential therapeutic implications as a better understanding of the molecular mechanisms underpinning the effects of ncRNAs on critical homeostatic control mechanisms and biochemical pathways might lead to the identification of novel druggable targets. In this context, increasing evidence suggests that several natural compounds can target ncRNAs at different levels and, consequently, influence processes involved in the onset and progression of disease states. The natural phenol resveratrol has been extensively studied for therapeutic purposes in view of its established anti-inflammatory and antioxidant effects, particularly in disease states such as cancer and cardiovascular disease that are associated with human aging. However, increasing in vitro and in vivo evidence also suggests that resveratrol can directly target various ncRNAs and that this mediates, at least in part, its potential therapeutic effects. This review critically appraises the available evidence regarding the resveratrol-mediated modulation of different ncRNAs in a wide range of disease states characterized by a pro-inflammatory state and oxidative stress, the potential therapeutic applications, and future research directions.